Identification and characterization of a new plasmid carrying genes for degradation of 2,4-dichlorophenoxyacetate from Pseudomonas cepacia CSV90. - Bhat, M A (1994)
Pseudomonas cepacia CSV90 is able to utilize 2,4-dichlorophenoxyacetate (2,4-D) and 2-methyl-4-chlorophenoxyacetate as sole sources of carbon and energy. Mutants of the strain CSV90 which had lost this ability appeared spontaneously on a nonselective medium. The wild-type strain harbored a 90-kb plasmid, pMAB1, whereas 2,4-D-negative mutants either lost the plasmid or had a 70-kb plasmid, pMAB2. The plasmid pMAB2 was found to have undergone a deletion of a 20-kb fragment of pMAB1. The plasmid-free mutants regained the ability to degrade 2,4-D after introduction of purified pMAB1 by electroporation. Cloning in Escherichia coli of a 10-kb BamHI fragment from pMAB1, the region absent in pMAB2, resulted in the expression of the gene tfdC encoding 3,5-dichlorocatechol 1,2-dioxygenase. After subcloning, the tfdC gene was located in a 1.6-kb HindIII fragment. The nucleotide sequence of the tfdC gene and the restriction map of its contiguous region are identical to those of the well-characterized 2,4-D-degradative plasmid pJP4 of Alcaligenes eutrophus, whereas the overall restriction maps of the two plasmids are different. The N-terminal 44-amino-acid sequence of the enzyme purified from the strain CSV90 confirmed the reading frame in the DNA sequence for tfdC and indicated that the initiation codon GUG is read as methionine instead of valine.